Eksploatacija pohorskih gozdov v preteklosti - Cimperšek, Mitja (Gozdarski vestnik, 2014)
Due to its unusual history and special forestry issues Pohorje occupies an important place among Slovenian regions. Beech primeval forests, iron ore, silicate rocks and numerous waterways attracted ironworkers and glaziers, eager of profit, to the mountain range. Ruthless exploitation had been in full swing in feudal forests at first, but, due to the development of sawmilling, timber rafting and wood trading, the peasants also began to apply excessive utilization measures in their forests. Unprofessional felling between 1750 and 1950 caused soil degradation, prevalence of spruce monocultures and complete transformation of the landscape.
Keywords: pragozd; železarstvo; steklarstvo; plavnica; splavarstvo; žagarstvo; trade; trgovina; bukev; smreka; Pohorje